“Descriptive Study to Assess the Knowledge Regarding the Risk Factors and Prevention of Myocardial Infarction Among Adults in Selected Urban Area at Kasaba Bawada Kolhapur” - Mr. Aman Waghmare; Mr. Amar Kamble; Mr. Amir Mulani; Mr. Aniket Gaikwad; Miss. Arpita Patil; Miss. Ankita Sawant; Miss. Dipti chorge; Mrs. Sonia shinde (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background and Objectives: Myocardial Infarction is one of the important heart disease. Understanding the risk factors of it may prevent the heart diseases among community. The researcher aims to assess the knowledge regarding the risk factors and prevention of Myocardial infarction Objectives: The objectives are as follows, 1. To assess the level of Knowledge regarding Myocardial Infarction among the adults. 2. To find association between level of knowledge with their selected socio demographic variables. Methods: In this study the Quantitative approach was used, the descriptive design was used , the study will be conducted in Selected areas of Kasaba Bawda Kolhapur, the selected sample was Adults ( 25-60 yrs) residing in Kasaba Bawada Kolhapur . Sample consists of 60 Adults. Result: In this study the the maximum number of adults 82 had average knowledge (82%), while adults 3 had poor knowledge. Conclusion: In present study; the out of 100 samples have knowledge about Myocardial Infraction among adults, 82 subjects had average knowledge, 15 subjects had good knowledge and 3 subjects had poor knowledge. The study focuses on need to create awareness regarding cardiovascular diseases and its prevention.